Student engagement and academic achievement: the effect of gamification on case and project-based online learning - Suartama, I Kadek; Sudarma, I Komang; Sudatha, I Gde Wawan; Sukmana, Adrianus I Wayan Ilia Yuda; Susiani, Ketut (Journal of Education and Learning (EduLearn), 2024)
Education is a pivotal pillar in modern society, and technology has brought about major changes in how students learn. Online learning is becoming an increasingly popular form of education, especially since the COVID-19 pandemic broke out. However, the challenge of maintaining student engagement and motivation in online learning environments remains a concern for many educators. This is where the concept of gamification erupts as an innovative solution to this problem. This study aimed to examine the effect of case- and project-based gamification models on student engagement and academic achievement in online learning in tertiary institutions. Quasi-experimental post-test only non-equivalent control group design was chosen as the method of this research. The subjects of this study were 117 students from Universitas Pendidikan Ganesha. The instrument used to measure student engagement was a questionnaire developed by researchers with reference to the online student engagement (OSE) indicator; meanwhile, an objective test was to assess student academic achievement. The data were analyzed using a one-way multivariate analysis of variance (MANOVA) technique. The study results show significant differences in student engagement and academic achievement between groups of students taught using case and project-based gamification models and direct e-learning models. Case and project-based gamification models used in online learning were effective in increasing student engagement and student academic achievement.